Validation of a risk prediction calculator in Australian patients undergoing head and neck microsurgery reconstruction. Issue 9 (September 2022) - Yung, Amanda E; Wong, Gerald; Pillinger, Neil; Wykes, James; Haddad, Roger; McInnes, Stephanie; Palme, Carsten E; (Hubert)Low, Tsu-Hui; Clark, Jonathan R; Sanders, Robert; Ch'ng, Sydney
Summary: Background: The American College of Surgeons (ACS) National Surgical Quality Improvement Program (NSQIP) surgical risk calculator (SRC) is an open access calculator predicting patients' risk of postoperative complications. This study aims to assess the validity of the SRC in patients undergoing microsurgical free flap reconstruction at an Australian tertiary referral centre. Methods: This is a retrospective cohort study of 200 consecutive patients treated up to November 2020. SRC-predicted rates of postoperative complications and hospital length of stay (LOS) were compared to those observed for the ablative and reconstructive components of the procedure. The performance of the SRC was assessed using Brier scores, area under the receiver operating characteristic (ROC) curve (AUC), and the Hosmer–Lemeshow test. Results: For both ablative and reconstructive components, the SRC discriminates well for pneumonia and urinary tract infection, and it is calibrated well for readmission and sepsis, but it does not discriminate and calibrate well for any single outcome. SRC-predicted hospital LOS and actual LOS did not correlate well for the reconstructive component, but they correlated strongly for the ablative component. Conclusions: The SRC is a poor predictor of postoperative complication rates and hospital LOS in patients undergoing head and neck microsurgical reconstruction.